Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

North American crayfish: A quest for the biggest catch - Caitlin C. Bloomer; Susan B. Adams; Zanethia C. Barnett; Zackary A. Graham; Emmy M. Delekta; David M. Hayes; Zachary J. Loughman; Hugh MacIntosh; M. Worth Pugh; Karen Reed; Nathaniel F. Shoobs; Christopher A. Taylor; et al. (Ecology, 2026)

Adventuring on thin ice: perceptions, adaptations, and adaptive capacity of Canadian mountaineers in the face of climate change - Brooklyn Rushton; Kate Hanly; Emmanuel Salim; Christopher J. Lemieux; Graham McDowell (Journal of Outdoor Recreation and Tourism, 2026)

Soil macropore characteristics and hydro-physical properties improved by diversified crop rotations and cover cropping in long-term no-till cropping systems - Sainfort Vital; Sutie Xu; Xi Zhang; Namrata Ghimire; Peter Sexton; Mengistu Geza; Christopher Graham; Lan Xu (Soil and Tillage Research, 2026)

Mind the Plateau: A Mathematical Modeling Analysis of Long-Term GLP-1 Receptor Agonist Treatment - Patrice A. Hubert; Christopher Coleman; Gregory J. Grosicki; Jessica Kiel; Madelyn Shepherd; Holly F. Lofton; Steven B. Heymsfield; J. Graham Thomas; Nikhil V. Dhurandhar; Satya S. Jonnalagadda (Journal of the Academy of Nutrition and Dietetics, 2026)

Neoproterozoic-Early Ordovician sedimentation on the eastern margin of Laurentia: A detrital zircon provenance perspective on the Dalradian Supergroup, Scotland and Ireland - Elias J. Rugen; Rob Strachan; David Chew; Jessica Molesworth; James Lee; Pieter Vermeesch; Dirk Frei; Andrew Morton; Zoe Whittaker; Craig Storey; Marina Seraine; Christopher L. Kirkland; et al. (Earth-Science Reviews, 2026)

High-resolution mapping and terrain classification of Halimeda bioherms in the northern Great Barrier Reef - Zsanett Szilagyi; Luke Nothdurft; Stephanie Duce; Jody M. Webster; Mardi McNeil; Robin J. Beaman; Juan Carlos Braga; Trevor Graham; Maria Byrne; Amy Nau; Christopher Berry; Victorien Paumard; et al. (Geomorphology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Contributions of benthic microalgal biofilms to sediment organic carbon stocks across a salt marsh gradient - Graham J. C. Underwood; Nicola J. D. Slee; Jessica C. J. Underwood; Christopher I. D. Underwood; James L. Pinckney (Limnology and Oceanography, 2026)
Benthic microalgal (BMA) communities contribute significantly to food webs, nutrient cycling, and carbon flows in intertidal habitats. However, the contribution of BMA to saltmarsh carbon stocks (“blue carbon”) is unclear. BMA and sediment total organic carbon (TOC) stocks were measured in an east coast American Atlantic saltmarsh, revealing key relationships between biofilm biomass, carbohydrate, and carbon content. BMA biomass (chlorophyll a ) was highest in Sporobolus stands and mudflat habitats, with diatoms the dominant algal group, and cyanobacteria more important in upper saltmarsh sites. Habitat‐specific differences in biofilm properties (biomass, carbohydrates, photopigments, near‐infrared spectra) corresponded to differences in overall contributions to sediment TOC. Carbohydrates contributed between 8% and 23% of sediment TOC, with the highest levels in Sporobolus and mudflat habitats. BMA biomass and colloidal carbohydrate were significantly correlated, except on lower shore sandflats. The greatest relative contribution of colloidal carbohydrate to %TOC was in upper marsh and tidal channel habitats (1%). Mudflats had the highest %TOC (up to 5% dry weight), but TOC stocks (2000 g C m −2 to a depth of 10 cm) were highest in Sporobolus habitats. A modeling approach, based on LIDAR and sediment measures, determined a BMA carbon contribution of 1.3–8% of sediment TOC, with the lowest values in Sporobolus and mudflat habitats. Upscaling from m 2 , incorporating habitat heterogeneity, gave median values of 14–16 t TOC ha −1 for the North Inlet Estuary saltmarshes, of which BMA contributed 0.06–0.08 t C ha −1 . This approach could permit BMA contributions to blue carbon to be estimated across other saltmarshes.

Emerging and persistent organic pollutants in sediment cores from the Singapore Straits: Rising pharmaceuticals, variable caffeine and static PAHs - Christopher H. Vane; Raquel A. Lopes dos Santos; Olivia A. Graham; Benjamin P. Horton; Mark C. Kalra; Vicky Moss-Hayes (Marine Pollution Bulletin, 2025)

The University of Oklahoma Inpatient Spine Protocol: optimizing surgical outcomes through standardized perioperative care - David Barkyoumb; William C. Kaiser; Lonnie Smith; Lance M. Villeneuve; Graham Mulvaney; Chao Li; Christopher S. Graffeo; Andrew M. Bauer; Hakeem J. Shakir; Karl Balsara; M. Burhan Janjua; John F. Burke; et al. (GeroScience, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

What to Measure in Aneurysmal Subarachnoid Haemorrhage Research—An International Delphi Survey - Christopher R. Andersen; Justin Presseau; Bev Shea; Maria Luisa Marti; Madeline McCoy; Gordon Fernie; Lauralyn McIntyre; Anthony Delaney; Michaël Chassé; Victoria Saigle; Shawn Marshall; Dean A. Fergusson; et al. (Translational Stroke Research, 2025)

Is sexual size dimorphism in walleye, Sander vitreus , a driver of seasonal movements in Lake Erie? - Christian J. Bihun; Matthew D. Faust; Richard T. Kraus; Thomas M. MacDougall; Jason M. Robinson; Christopher S. Vandergoot; Graham D. Raby (Journal of Fish Biology, 2025)
Walleye ( Sander vitreus ) are a sexually dimorphic species in which females are larger than males in adulthood. Walleye can also exhibit sex‐ and population‐based differences in migration behavior. In Lake Erie, we used acoustic telemetry to test the prediction that female walleye exhibit larger broad‐scale movements than males during the summer and autumn. This prediction was based on the hypothesis that greater foraging in females would be needed to satisfy their higher energy requirements. We quantified movements of males and females from distinct spawning populations from Lake Erie's west and east basins using a lake‐wide grid of acoustic receivers in 2017 and 2018. We found no differences between male and female home range sizes, core range sizes, or distances travelled in either population. Fish length‐at‐tagging was unrelated to the size of a fish's home range or to its distance travelled, contrary to previous predictions about body size as a driver of migration distance in the Lake Erie population. We found that west basin walleye occupied large and indiscrete portions of the lake, but the core range of females extended into the central basin, whereas males were concentrated in the west basin. Walleye originating from the east basin confined their movements primarily to the east basin and showed stronger home range overlap among members of their population than did walleye from the west basin population. Within either population, walleye had more home range overlap with members of the same sex, which likely reflects differences in the migratory tendencies of males and females.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Secular evolution of continental crust of the North China Craton constrained by U-Pb and Lu-Hf-O/Sm-Nd isotopic analyses of detrital zircon and monazite in river sediments - Guangyan Zhou; D. Graham Pearson; Yan Luo; Long Li; Christopher M. Fisher; Rui Li; Wei Wang; Yuanbao Wu (Chemical Geology, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

The role of Geographic Information Systems in mitigating plastics pollution in the Global South—A spatial analysis of recycling facilities in Costa Rica - Christopher C. Graham (Science of The Total Environment, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Early Eocene Arctic volcanism from carbonate-metasomatized mantle - James M. D. Day; D. Graham Pearson; Bruce A. Kjarsgaard; Abigail K. Barker; Geoff M. Nowell; Nancy Joyce; David Lowry; Chiranjeeb Sarkar; Christopher Harrison (Contributions to Mineralogy and Petrology, 2023)
Melilitite, nephelinite, basanite, and alkali basalt, along with phonolite differentiates, form the Freemans Cove Complex (FCC) in the south-eastern extremity of Bathurst Island (Nunavut, Canada). New 40 Ar/ 39 Ar chronology indicates their emplacement between ~ 56 and ~ 54 million years ago within a localized extensional structure. Melilitites and nephelinites, along with phonolite differentiates, likely relate to the beginning and end phases of extension, whereas alkali basalts were emplaced during a main extensional episode at ~ 55 Ma. The melilitites, nephelinites, and alkali basalts show no strong evidence for significant assimilation of crust, in contrast to some phonolites. Partial melting occurred within both the garnet- and spinel-facies mantle and sampled sources with He, O, Nd, Hf, and Os isotope characteristics indicative of peridotite with two distinct components. The first, expressed in higher degree partial melts, represents a relatively depleted component (“A”; 3 He/ 4 He ~ 8 R A , ε Nd i ~ + 3 ε Hf i ~ + 7, γ Os i ~ 0). The second was an enriched component (“B” 3 He/ 4 He < 3 R A , ε Nd i < – 1 ε Hf i < + 3, γ Os i > + 70) sampled by the lowest degree partial melts and represents carbonate-metasomatized peridotite. Magmatism in the FCC shows that rifting extended from the Labrador Sea to Bathurst Island and reached a zenith at ~ 55 Ma, during the Eurekan orogeny. The incompatible trace-element abundances and isotopic signatures of FCC rocks indicate melt generation occurred at the base of relatively thin lithosphere at the margin of a thick craton, with no mantle plume influence. FCC melt compositions are distinct from other continental rift magmatic provinces worldwide, and their metasomatized mantle source was plausibly formed synchronously with emplacement of Cretaceous kimberlites. The FCC illustrates that the range of isotopic compositions preserved in continental rift magmas are likely to be dominated by temporal changes in the extent of partial melting, as well as by the timing and degree of metasomatism recorded in the underlying continental lithosphere.

Not just range limits: Warming rate and thermal sensitivity shape climate change vulnerability in a species range center - Fiona Beaty; Alyssa‐Lois M. Gehman; Graham Brownlee; Christopher D. G. Harley (Ecology, 2023)
Climate change manifests unevenly across space and time and produces complex patterns of stress for ecological systems. Species can also show substantial among‐population variability in response to environmental change across their geographic range due to evolutionary processes. Explanatory factors or their proxies, such as temperature and latitude, help parse these sources of environmental and intraspecific variability; however, overemphasizing latitudinal trends can obscure the role of local environmental conditions in shaping population vulnerability to climate change. Focusing on the geographic center of a species range to disentangle latitude, we test the hypothesis that populations from warmer regions of a species range are more vulnerable to ocean warming. We conducted a mesocosm experiment and field reciprocal transplant with four populations of a marine snail, Nucella lamellosa , from two regions in British Columbia, Canada, that differ in thermal characteristics: the Central Coast, a cool region, and the Strait of Georgia, one of the warmest regions of this species' range and one that is warming faster than the Central Coast. Populations from the Strait of Georgia experienced growth reductions at contemporary summertime seawater temperatures in the laboratory and showed stark reductions in survival and growth under future seawater conditions and when outplanted at their native transplant sites. This indicates a high vulnerability to ocean warming, especially given the faster rate of ocean warming in this region. In contrast, populations from the cooler Central Coast demonstrated high performance at contemporary seawater temperatures and high growth and survival in projected future seawater temperatures and at their native outplant sites. Given their position within the geographic center of N. lamellosa 's range, extirpation events in the vulnerable Strait of Georgia populations could compromise connectivity within the metapopulation and lead to gaps across this species' range. Overall, our study supports predictions that populations from warm regions of species ranges are more vulnerable to environmental warming, suggests that the Strait of Georgia and other inland or coastal seas could be focal points for climate change effects and ecological transformation, and emphasizes the importance of analyzing climate change vulnerability in the context of regional environmental data and throughout a species' range.

Smartwatch-Based Prediction of Single-Stride and Stride-to-Stride Gait Outcomes Using Regression-Based Machine Learning - Christopher A. Bailey; Alexandre Mir-Orefice; Thomas K. Uchida; Julie Nantel; Ryan B. Graham (Annals of Biomedical Engineering, 2023)

Skin decontamination of Carfentanil in vitro - Christopher Dalton; Rachel Watkins; Sarah Pritchard; Stuart Graham (Toxicology Letters, 2023)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Harvest index has increased over the last 50 years of maize breeding - Alejo Ruiz; Slobodan Trifunovic; Douglas M. Eudy; Cintia S. Sciarresi; Mitchell Baum; Gerasimos J.N. Danalatos; Elvis F. Elli; Georgios Kalogeropoulos; Kyle King; Caio dos Santos; August Thies; Lia Olmedo Pico; et al. (Field Crops Research, 2023)

Co-designing a multi-criteria approach to ranking hazards to and from Australia’s emerging offshore blue economy - Mischa P. Turschwell; Christopher J. Brown; Myriam Lacharité; Jess Melbourne-Thomas; Keith R. Hayes; Rodrigo H. Bustamante; Jeffrey M. Dambacher; Karen Evans; Pedro Fidelman; Darla Hatton MacDonald; Ingrid Van Putten; Graham Wood; et al. (Environmental Science & Policy, 2023)

Applications of Natural Language Processing to Geoscience Text Data and Prospectivity Modeling - Christopher J. M. Lawley; Michael G. Gadd; Mohammad Parsa; Graham W. Lederer; Garth E. Graham; Arianne Ford (Natural Resources Research, 2023)
Geological maps are powerful models for visualizing the complex distribution of rock types through space and time. However, the descriptive information that forms the basis for a preferred map interpretation is typically stored in geological map databases as unstructured text data that are difficult to use in practice. Herein we apply natural language processing (NLP) to geoscientific text data from Canada, the U.S., and Australia to address that knowledge gap. First, rock descriptions, geological ages, lithostratigraphic and lithodemic information, and other long-form text data are translated to numerical vectors, i.e., a word embedding, using a geoscience language model. Network analysis of word associations, nearest neighbors, and principal component analysis are then used to extract meaningful semantic relationships between rock types. We further demonstrate using simple Naive Bayes classifiers and the area under receiver operating characteristics plots (AUC) how word vectors can be used to: (1) predict the locations of “pegmatitic” (AUC = 0.962) and “alkalic” (AUC = 0.938) rocks; (2) predict mineral potential for Mississippi-Valley-type (AUC = 0.868) and clastic-dominated (AUC = 0.809) Zn-Pb deposits; and (3) search geoscientific text data for analogues of the giant Mount Isa clastic-dominated Zn-Pb deposit using the cosine similarities between word vectors. This form of semantic search is a promising NLP approach for assessing mineral potential with limited training data. Overall, the results highlight how geoscience language models and NLP can be used to extract new knowledge from unstructured text data and reduce the mineral exploration search space for critical raw materials.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Number of COVID-19 cases required in a population to detect SARS-CoV-2 RNA in wastewater in the province of Alberta, Canada: Sensitivity assessment - Qiaozhi Li; Bonita E. Lee; Tiejun Gao; Yuanyuan Qiu; Erik Ellehoj; Jiaao Yu; Mathew Diggle; Graham Tipples; Rasha Maal-Bared; Deena Hinshaw; Christopher Sikora; Nicholas J. Ashbolt; et al. (Journal of Environmental Sciences, 2023)

Trace metal and sulfur cycling in a hydrothermally active arc volcano: deep-sea drilling of the Brothers volcano, Kermadec arc, New Zealand - Andrew J. Martin; John W. Jamieson; Cornel E. J. de Ronde; Susan E. Humphris; Iain McDonald; Graham D. Layne; Glenn Piercey; Christopher J. MacLeod (Mineralium Deposita, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Mineral-scale variation in the trace metal and sulfur isotope composition of pyrite: implications for metal and sulfur sources in mafic VMS deposits - Andrew J. Martin; Iain McDonald; John W. Jamieson; Gawen R. T. Jenkin; Katie A. McFall; Glenn Piercey; Christopher J. MacLeod; Graham D. Layne (Mineralium Deposita, 2022)

Cardiac activity in walleye ( Sander vitreus ) during exposure to and recovery from chemical anaesthesia, electroanaesthesia and electrostunning - Connor H. Reid; Graham D. Raby; Matthew D. Faust; Steven J. Cooke; Christopher S. Vandergoot (Journal of Fish Biology, 2022)
Handling and conducting invasive procedures are necessary for aspects of fisheries science, invariably inducing a stress response and imposing energetic demands on fish. Anaesthesia or immobilisation techniques are often used in an attempt to mitigate stress and improve welfare, yet these also come with their own impacts on post‐release recovery. Here, the authors investigated whether changes in cardiac activity (heart rates over time, heart rate maxima, and scopes) differed in adult walleye ( Sander vitreus ) anaesthetised with AQUI‐S® 20E (eugenol), electroanaesthetised with a transcutaneous electrical nerve stimulation (TENS) unit or electrostunned with a commercially developed stunning unit. This experiment was divided into two trials. In the first trial, fish were implanted with heart rate loggers and left to recover for c. 4 days. In the second trial, fish were implanted with heart rate loggers, given 3 days to recover and re‐exposed to their initial treatments (excluding surgery). Post‐treatment cardiac activity was quantified for both trials. Although highly variable across individuals, the authors found no significant differences in heart rate changes over time or recovery times among treatments. Maximum heart rates were consistent among treatment groups, yet significant differences in heart rate scope provided further evidence of strong interindividual variation in the second trial. Based on these results, the authors did not identify any welfare‐relevant differences or concerns associated with one treatment over another. Further investigations of the relationships between measures of cardiac function and other physiological stress markers would be beneficial towards identifying best practices for fish handling in fisheries science.

The contribution of macroalgae‐associated fishes to small‐scale tropical reef fisheries - Shaun K. Wilson; Christopher J. Fulton; Nicholas A.J. Graham; Rene A. Abesamis; Charlotte Berkström; Darren J. Coker; Martial Depczynski; Richard D. Evans; Rebecca Fisher; Jordan Goetze; Andrew Hoey; Thomas H. Holmes; et al. (Fish and Fisheries, 2022)
Macroalgae‐dominated reefs are a prominent habitat in tropical seascapes that support a diversity of fishes, including fishery target species. To what extent, then, do macroalgal habitats contribute to small‐scale tropical reef fisheries? To address this question we: (1) Quantified the macroalgae‐associated fish component in catches from 133 small‐scale fisheries, (2) Compared life‐history traits relevant to fishing (e.g. growth, longevity) in macroalgal and coral‐associated fishes, (3) Examined how macroalgae‐associated species can influence catch diversity, trophic level and vulnerability and (4) Explored how tropical fisheries change with the expansion of macroalgal habitats using a case study of fishery‐independent data for Seychelles. Fish that utilised macroalgal habitats comprise 24% of the catch, but very few fished species relied entirely on macroalgal or coral habitats post‐settlement. Macroalgal and coral‐associated fishes had similar life‐history traits, although vulnerability to fishing declined with increasing contribution of macroalgae association to the catch, whilst mean trophic level and diversity peaked when macroalgal‐associated fish accounted for 20%–30% of catches. The Seychelles case study revealed similar total fish biomass on macroalgal and coral reefs, although the biomass of primary target species increased as macroalgae cover expanded. Our findings reinforce that multiple habitat types are needed to support tropical fishery stability and sustainability. Whilst coral habitats have been the focus of tropical fisheries management, we show the potential for macroalgae‐associated fish to support catch size and diversity in ways that reduce vulnerability to overfishing. This is pertinent to seascapes where repeated disturbances are facilitating the replacement of coral reef with macroalgal habitats.

Connecting to the oceans: supporting ocean literacy and public engagement - Rachel Kelly; Karen Evans; Karen Alexander; Silvana Bettiol; Stuart Corney; Coco Cullen-Knox; Christopher Cvitanovic; Kristy de Salas; Gholam Reza Emad; Liam Fullbrook; Carolina Garcia; Sierra Ison; et al. (Reviews in Fish Biology and Fisheries, 2022)

Ecological-Fishery Forecasting of Squid Stock Dynamics under Climate Variability and Change: Review, Challenges, and Recommendations - Hassan Moustahfid; Lisa C. Hendrickson; Alexander Arkhipkin; Graham J. Pierce; Avijit Gangopadhyay; Hideaki Kidokoro; Unai Markaida; Chingiz Nigmatullin; Warwick H. Sauer; Patrizia Jereb; Gretta Pecl; Thibaut de la Chesnais; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Assessment of Numerical Methods for Plunging Breaking Wave Predictions - Shanti Bhushan; Oumnia El Fajri; Graham Hubbard; Bradley Chambers; Christopher Kees (Journal of Marine Science and Engineering, 2021)
This study evaluates the capability of Navier–Stokes solvers in predicting forward and backward plunging breaking, including assessment of the effect of grid resolution, turbulence model, and VoF, CLSVoF interface models on predictions. For this purpose, 2D simulations are performed for four test cases: dam break, solitary wave run up on a slope, flow over a submerged bump, and solitary wave over a submerged rectangular obstacle. Plunging wave breaking involves high wave crest, plunger formation, and splash up, followed by second plunger, and chaotic water motions. Coarser grids reasonably predict the wave breaking features, but finer grids are required for accurate prediction of the splash up events. However, instabilities are triggered at the air–water interface (primarily for the air flow) on very fine grids, which induces surface peel-off or kinks and roll-up of the plunger tips. Reynolds averaged Navier–Stokes (RANS) turbulence models result in high eddy-viscosity in the air–water region which decays the fluid momentum and adversely affects the predictions. Both VoF and CLSVoF methods predict the large-scale plunging breaking characteristics well; however, they vary in the prediction of the finer details. The CLSVoF solver predicts the splash-up event and secondary plunger better than the VoF solver; however, the latter predicts the plunger shape better than the former for the solitary wave run-up on a slope case.

Direct and indirect effects of heatwaves on a coral reef fishery - Christopher J. Brown; Camille Mellin; Graham J. Edgar; Max D. Campbell; Rick D. Stuart‐Smith (Global Change Biology, 2021)
Marine heatwaves are increasing in frequency and intensity, and indirectly impacting coral reef fisheries through bleaching‐induced degradation of live coral habitats. Marine heatwaves also affect fish metabolism and catchability, but such direct effects of elevated temperatures on reef fisheries are largely unknown. We investigated direct and indirect effects of the devastating 2016 marine heatwave on the largest reef fishery operating along the Great Barrier Reef (GBR). We used a combination of fishery‐independent underwater census data on coral trout biomass ( Plectropomus and Variola spp.) and catch‐per‐unit‐effort (CPUE) data from the commercial fishery to evaluate changes in the fishery resulting from the 2016 heatwave. The heatwave caused widespread, yet locally patchy, declines in coral cover, but we observed little effect of local coral loss on coral trout biomass. Instead, a pattern of decreasing biomass at northern sites and stable or increasing biomass at southern sites suggested a direct response of populations to the heatwave. Analysis of the fishery‐independent data and CPUE found that in‐water coral trout biomass estimates were positively related to CPUE, and that coral trout catch rates increased with warmer temperatures. Temperature effects on catch rates were consistent with the thermal affinities of the multiple species contributing to this fishery. Scaling‐up the effect of temperature on coral trout catch rates across the region suggests that GBR‐wide catches were 18% higher for a given level of effort during the heatwave year relative to catch rates under the mean temperatures in the preceding 6 years. These results highlight a potentially large effect of heatwaves on catch rates of reef fishes, independent of changes in reef habitats, that can add substantial uncertainty to estimates of stock trends inferred from fishery‐dependent (CPUE) data. Overestimation of CPUE could initiate declines in reef fisheries that are currently fully exploited, and threaten sustainable management of reef stocks.

Global data set for nitrogen and carbon stable isotopes of tunas - Nathalie Bodin; Heidi Pethybridge; Leanne M. Duffy; Anne Lorrain; Valérie Allain; John M. Logan; Frédéric Ménard; Brittany Graham; C. Anela Choy; Christopher J. Somes; Robert J. Olson; Jock W. Young (Ecology, 2021)
Nitrogen and carbon stable isotope data sets are commonly used to assess complex population to ecosystem responses to natural or anthropogenic changes at regional to global spatial scales, and monthly to decadal timescales. Measured in the tissues of consumers, nitrogen isotopes (δ 15 N) are primarily used to estimate trophic position while carbon isotopes (δ 13 C) describe habitat associations and feeding pathways. Models of both δ 15 N and δ 13 C values and their associated variance can be used to estimate likely dietary contributions and niche width and provide inferences about consumer movement and migration. Stable isotope data have added utility when used in combination with other empirical data sets (e.g., stomach content, movement tracking, bioregionalization, contaminant, or fisheries data) and are increasingly relied upon in food web and ecosystem models. While numerous regional studies publish tables of mean δ 15 N and δ 13 C values, limited individual records have been made available for wider use. Such a deficiency has impeded full utility of the data, which otherwise would facilitate identification of macroscale patterns. The data provided here consist of 4,498 records of individuals of three tuna species, Thunnus alalunga , T. obesus , and T. albacares sampled from all major ocean basins from 2000 to 2015. For each individual tuna, we provide a record of the following: species name, sampling date, sampling location, tuna length, muscle bulk and baseline corrected δ 15 N values, and muscle bulk and, where available, lipid corrected δ 13 C values. We provide these individual records to support comparative studies and more robust modeling projects seeking to improve understanding of complex marine ecosystem dynamics and their responses to a changing environment. There are no copyright restrictions for research and/or teaching purposes. Users are requested to acknowledge their use of the data in publications, research proposals, websites, and other outlets following the citation instructions in Class III, Section B.

Responder Needs Addressed by Arctic Maritime Oil Spill Modeling - Jessica Manning; Megan Verfaillie; Christopher Barker; Catherine Berg; Amy MacFadyen; Michael Donnellan; Mark Everett; Clifton Graham; Jason Roe; Nancy Kinner (Journal of Marine Science and Engineering, 2021)
There is a greater probability of more frequent and/or larger oil spills in the Arctic region due to increased maritime shipping and natural resource development. Accordingly, there is an increasing need for effective spilled-oil computer modeling to help emergency oil spill response decision makers, especially in waters where sea ice is present. The National Oceanic & Atmospheric Administration (NOAA) Office of Response & Restoration (OR&R) provides scientific support to the U.S. Coast Guard Federal On-Scene Coordinator (FOSC) during oil spill response. OR&R’s modeling products must provide adequate spill trajectory predictions so that response efforts minimize economic, cultural, and ecologic impacts, including those to species, habitats, and food supplies. The Coastal Response Research Center is conducting a project entitled Oil Spill Modeling for Improved Response to Arctic Maritime Spills: The Path Forward, in conjunction with modelers, responders, and researchers. A goal of the project is to prioritize new investments in model and tool development to improve response effectiveness in the Arctic. The project delineated FOSC needs during Arctic maritime spill response and provided a solution communicating sources of uncertainty in model outputs using a Confidence Estimates of Oil Model Inputs and Outputs (CEOMIO) table. The table shows the level of confidence (high, medium, low) in a model’s trajectory prediction over scenario-specific time intervals and the contribution of different component inputs (e.g., temperature, wind, ice) to that result.

Lung abnormalities do not influence aerobic capacity in school children born preterm - Christopher A. O’Dea; Karla Logie; Andrew C. Wilson; J. Jane Pillow; Conor Murray; Georgia Banton; Shannon J. Simpson; Graham L. Hall; Andrew Maiorana (European Journal of Applied Physiology, 2021)

Effects of urbanisation and landscape heterogeneity mediated by feeding guild and body size in a community of coprophilous beetles - Christopher W. Foster; Christopher Kelly; Jordan J. Rainey; Graham J. Holloway (Urban Ecosystems, 2020)
Although the impacts of urbanisation on biodiversity are well studied, the precise response of some invertebrate groups remains poorly known. Dung-associated beetles are little studied in an urban context, especially in temperate regions. We considered how landscape heterogeneity, assessed at three spatial scales (250, 500 and 1000 m radius), mediates the community composition of coprophilous beetles on a broad urban gradient. Beetles were sampled using simple dung-baited traps, placed at 48 sites stratified across three distance bands around a large urban centre in England. The most urban sites hosted the lowest abundance of saprophagous beetles, with a lower mean body length relative to the least urban sites. Predicted overall species richness and the richness of saprophagous species were also lowest at the most urban sites. Ordination analyses followed by variation partitioning revealed that landscape heterogeneity across the urban gradient explained a small but significant proportion of community composition. Heterogeneity data for a 500-m radius around each site provided the best fit with beetle community data. Larger saprophagous species were associated with lower amounts of manmade surface and improved grassland. Some individual species, particularly predators, appeared to be positively associated with urban or urban fringe sites. This study is probably the first to examine the response of the whole coprophilous beetle community to urbanisation. Our results suggest that the response of this community to urbanisation matches expectations based on other taxonomic groups, whilst emphasising the complex nature of this response, with some smaller-bodied species potentially benefitting from urbanisation.

Macroalgal meadow habitats support fish and fisheries in diverse tropical seascapes - Christopher J. Fulton; Charlotte Berkström; Shaun K. Wilson; Rene A. Abesamis; Michael Bradley; Carolina Åkerlund; Luke T. Barrett; Abner A. Bucol; Dinorah H. Chacin; Karen M. Chong‐Seng; Darren J. Coker; Martial Depczynski; et al. (Fish and Fisheries, 2020)
Canopy‐forming macroalgae can construct extensive meadow habitats in tropical seascapes occupied by fishes that span a diversity of taxa, life‐history stages and ecological roles. Our synthesis assessed whether these tropical macroalgal habitats have unique fish assemblages, provide fish nurseries and support local fisheries. We also applied a meta‐analysis of independent surveys across 23 tropical reef locations in 11 countries to examine how macroalgal canopy condition is related to the abundance of macroalgal‐associated fishes. Over 627 fish species were documented in tropical macroalgal meadows, with 218 of these taxa exhibiting higher local abundance within this habitat (cf. nearby coral reef) during at least one life‐history stage. Major overlap (40%–43%) in local fish species richness among macroalgal and seagrass or coral reef habitats suggest macroalgal meadows may provide an important habitat refuge. Moreover, the prominence of juvenile fishes suggests macroalgal meadows facilitate the triphasic life cycle of many fishes occupying diverse tropical seascapes. Correlations between macroalgal canopy structure and juvenile abundance suggests macroalgal habitat condition can influence levels of replenishment in tropical fish populations, including the majority of macroalgal‐associated fishes that are targeted by commercial, subsistence or recreational fisheries. While many macroalgal‐associated fishery species are of minor commercial value, their local importance for food and livelihood security can be substantial (e.g. up to 60% of landings in Kenyan reef fisheries). Given that macroalgal canopy condition can vary substantially with sea temperature, there is a high likelihood that climate change will impact macroalgal‐associated fish and fisheries.

Trends in tuna carbon isotopes suggest global changes in pelagic phytoplankton communities - Anne Lorrain; Heidi Pethybridge; Nicolas Cassar; Aurore Receveur; Valérie Allain; Nathalie Bodin; Laurent Bopp; C. Anela Choy; Leanne Duffy; Brian Fry; Nicolas Goñi; Brittany S. Graham; et al. (Global Change Biology, 2020)
Considerable uncertainty remains over how increasing atmospheric CO 2 and anthropogenic climate changes are affecting open‐ocean marine ecosystems from phytoplankton to top predators. Biological time series data are thus urgently needed for the world's oceans. Here, we use the carbon stable isotope composition of tuna to provide a first insight into the existence of global trends in complex ecosystem dynamics and changes in the oceanic carbon cycle. From 2000 to 2015, considerable declines in δ 13 C values of 0.8‰–2.5‰ were observed across three tuna species sampled globally, with more substantial changes in the Pacific Ocean compared to the Atlantic and Indian Oceans. Tuna recorded not only the Suess effect, that is, fossil fuel‐derived and isotopically light carbon being incorporated into marine ecosystems, but also recorded profound changes at the base of marine food webs. We suggest a global shift in phytoplankton community structure, for example, a reduction in 13 C‐rich phytoplankton such as diatoms, and/or a change in phytoplankton physiology during this period, although this does not rule out other concomitant changes at higher levels in the food webs. Our study establishes tuna δ 13 C values as a candidate essential ocean variable to assess complex ecosystem responses to climate change at regional to global scales and over decadal timescales. Finally, this time series will be invaluable in calibrating and validating global earth system models to project changes in marine biota.

Petrology of the 2016–2017 eruption of Bogoslof Island, Alaska - Matthew W. Loewen; Pavel Izbekov; Jamshid Moshrefzadeh; Michelle Coombs; Jessica Larsen; Nathan Graham; Michelle Harbin; Christopher Waythomas; Kristi Wallace (Bulletin of Volcanology, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Conducting and interpreting fish telemetry studies: considerations for researchers and resource managers - Jacob W. Brownscombe; Elodie J. I. Lédée; Graham D. Raby; Daniel P. Struthers; Lee F. G. Gutowsky; Vivian M. Nguyen; Nathan Young; Michael J. W. Stokesbury; Christopher M. Holbrook; Travis O. Brenden; Christopher S. Vandergoot; Karen J. Murchie; et al. (Reviews in Fish Biology and Fisheries, 2019)

Identification and characterization of a novel anti-inflammatory lipid isolated from Mycobacterium vaccae, a soil-derived bacterium with immunoregulatory and stress resilience properties - David G. Smith; Roberta Martinelli; Gurdyal S. Besra; Petr A. Illarionov; Istvan Szatmari; Peter Brazda; Mary A. Allen; Wenqing Xu; Xiang Wang; László Nagy; Robin D. Dowell; Graham A. W. Rook; et al. (Psychopharmacology, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Recruitment tolerance to increased temperature present across multiple kelp clades - Arley F. Muth; Michael H. Graham; Christopher E. Lane; Christopher D. G. Harley (Ecology, 2019)
Kelp systems dominate nearshore marine environments in upwelling zones characterized by cold temperatures and high nutrients. Worldwide, kelp population persistence and recruitment success generally decreases with rising water temperatures coupled with low nutrients, making kelp populations vulnerable to impending warming of the oceans. This response to climate change at a global scale, however, may vary due to regional differences in temperature variability, acclimation, and differential responses of kelp species to changing conditions. Culture experiments were conducted on 12 eastern Pacific kelp taxa across geographic regions (British Columbia, central California, and southern California) under three nitrate levels (1, 5, and 10 μmol/L) and two temperatures (12°C and 18°C) to determine sporophyte production (i.e., recruitment success). For all taxa from all locations, sporophytes were always present in the 12°C treatment and when recruitment failure was observed, it always occurred at 18°C, regardless of nitrate level, indicating that temperature is the driving factor limiting recruitment, not nitrate. Rising ocean temperatures will undoubtedly cause recruitment failure for many kelp species; however, the ability of species to acclimatize or adapt to increased temperatures at the warmer edge of their species range may promote a resiliency of kelp systems to climate change at a global scale.

Mitochondrial health and muscle plasticity after spinal cord injury - Ashraf S. Gorgey; Oksana Witt; Laura O’Brien; Christopher Cardozo; Qun Chen; Edward J. Lesnefsky; Zachary A. Graham (European Journal of Applied Physiology, 2019)

Presence of an invasive species reverses latitudinal clines of multiple traits in a native species - Christopher J. Thawley; Mark Goldy‐Brown; Gail L. McCormick; Sean P. Graham; Tracy Langkilde (Global Change Biology, 2019)
Understanding the processes driving formation and maintenance of latitudinal clines has become increasingly important in light of accelerating global change. Many studies have focused on the role of abiotic factors, especially temperature, in generating clines, but biotic factors, including the introduction of non‐native species, may also drive clinal variation. We assessed the impact of invasion by predatory fire ants on latitudinal clines in multiple fitness‐relevant traits—morphology, physiological stress responsiveness, and antipredator behavior—in a native fence lizard. In areas invaded by fire ants, a latitudinal cline in morphology is opposite both the cline found in museum specimens from historical populations across the species’ full latitudinal range and that found in current populations uninvaded by fire ants. Similarly, clines in stress‐relevant hormone response to a stressor and in antipredator behavior differ significantly between the portions of the fence lizard range invaded and uninvaded by fire ants. Changes in these traits within fire ant‐invaded areas are adaptive and together support increased and more effective antipredator behavior that allows escape from attacks by this invasive predator. However, these changes may mismatch lizards to the environments under which they historically evolved. This research shows that novel biotic pressures can alter latitudinal clines in multiple traits within a single species on ecological timescales. As global change intensifies, a greater understanding of novel abiotic and biotic pressures and how affected organisms adapt to them across space and time will be central to predicting and managing our changing environment.

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Direct Quantification of Solute Diffusivity in Agarose and Articular Cartilage Using Correlation Spectroscopy - Janty S. Shoga; Brian T. Graham; Liyun Wang; Christopher Price (Annals of Biomedical Engineering, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Joint associations of blood plasma proteins with overwinter survival of a large mammal - Romain Garnier; Christopher K. Cheung; Kathryn A. Watt; Jill G. Pilkington; Josephine M. Pemberton; Andrea L. Graham (Ecology Letters, 2017)
In many wild animal populations, hosts are at risk of parasites and malnutrition and resource costs of defence may be difficult to afford. We postulate that proteins, important in homeostasis and immunity, play a complex but central role in condition dependence and resource costs of mammalian immune defence. To test this, we measured plasma concentrations of albumin, total proteins. Self‐reactive antibodies and parasite‐specific IgG in female Soay sheep. Using a principal component analysis, we found a new metric of condition reflecting individual variation in acquisition, assimilation and/or recycling of plasma proteins that predicted overwinter survival. Controlling for this metric, an age‐dependent trade‐off between antibody titres and protein reserves emerged, indicating costs of mounting an antibody response: younger individuals survived best when prioritising immunity while older individuals fared better when maintaining high‐protein nutritional plane. These findings suggest fascinating roles for protein acquisition and allocation in influencing survival in wild animal populations.

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Species specificity of temporal processing in the auditory midbrain of gray treefrogs: long-interval neurons - Jessica L. Hanson; Gary J. Rose; Christopher J. Leary; Jalina A. Graham; Rishi K. Alluri; Gustavo A. Vasquez-Opazo (Journal of Comparative Physiology A, 2016)

Within‐river genetic connectivity patterns reflect contrasting geomorphology - Jonathan M. Waters; Dave Craw; Christopher P. Burridge; Martyn Kennedy; Tania M. King; Graham P. Wallis (Journal of Biogeography, 2015)
Aim To test the hypothesis that geomorphological features, shaped by underlying geology, can influence within‐river connectivity patterns in freshwater‐limited fishes. Location Rivers draining the eastern flanks of the Southern Alps in South Island, New Zealand. Methods We analyse up to 1624 bp of mt DNA from 499 ‘flathead’ Galaxias specimens from 145 localities across 14 different river systems. Variation among sampling sites within systems is characterized using ϕ statistics. Results Although similar levels of DNA sequence variation were detected in all rivers sampled, spatial partitioning of this variation was significantly greater within schist ( n = 5; mean ϕ ST = 0.696) than within greywacke ( n = 10; mean ϕ ST = 0.268) rivers. Main conclusions Population connectivity can be strongly influenced by underlying geology, leading to profound differences in the connectivity, phylogeography and diversity of riverine species.

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Focal adhesion kinase and its role in skeletal muscle - Zachary A. Graham; Philip M. Gallagher; Christopher P. Cardozo (Journal of Muscle Research and Cell Motility, 2015)

Species-specificity of temporal processing in the auditory midbrain of gray treefrogs: interval-counting neurons - Gary J. Rose; Jessica L. Hanson; Christopher J. Leary; Jalina A. Graham; Rishi K. Alluri; Gustavo A. Vasquez-Opazo (Journal of Comparative Physiology A, 2015)

Identification of Proteins Associated with Adhesive Prints from Holothuria dofleinii Cuvierian Tubules - Yong Y. Peng; Veronica Glattauer; Timothy D. Skewes; Andrew McDevitt; Christopher M. Elvin; Jerome A. Werkmeister; Lloyd D. Graham; John A. M. Ramshaw (Marine Biotechnology, 2014)

Basal metabolism of an adult male killer whale ( Orcinus orca ) - Graham A. J. Worthy; Tamara A. M. Worthy; Pamela K. Yochem; Christopher Dold (Marine Mammal Science, 2014)

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Exercise-induced oxidative stress and hypoxic exercise recovery - Christopher Ballmann; Graham McGinnis; Bridget Peters; Dustin Slivka; John Cuddy; Walter Hailes; Charles Dumke; Brent Ruby; John Quindry (European Journal of Applied Physiology, 2014)

Implications of Macroalgal Isolation by Distance for Networks of Marine Protected Areas - HALLEY M. S. DURRANT; CHRISTOPHER P. BURRIDGE; BRENDAN P. KELAHER; NEVILLE S. BARRETT; GRAHAM J. EDGAR; MELINDA A. COLEMAN (Conservation Biology, 2014)
The global extent of macroalgal forests is declining, greatly affecting marine biodiversity at broad scales through the effects macroalgae have on ecosystem processes, habitat provision, and food web support. Networks of marine protected areas comprise one potential tool that may safeguard gene flow among macroalgal populations in the face of increasing population fragmentation caused by pollution, habitat modification, climate change, algal harvesting, trophic cascades, and other anthropogenic stressors. Optimal design of protected area networks requires knowledge of effective dispersal distances for a range of macroalgae. We conducted a global meta‐analysis based on data in the published literature to determine the generality of relation between genetic differentiation and geographic distance among macroalgal populations. We also examined whether spatial genetic variation differed significantly with respect to higher taxon, life history, and habitat characteristics. We found clear evidence of population isolation by distance across a multitude of macroalgal species. Genetic and geographic distance were positively correlated across 49 studies; a modal distance of 50–100 km maintained F ST Implicaciones del Aislamiento por Distancia de Macroalgas para Redes de Áreas Marinas Protegidas

Nitrous oxide emissions are greater in silt loam soils with a legacy of manure application than without - Christopher J. Graham; Harold M. van Es; Jeffrey J. Melkonian (Biology and Fertility of Soils, 2013)

Waterbird use of artificial wetlands in an Australian urban landscape - Christopher G. Murray; Sabine Kasel; Richard H. Loyn; Graham Hepworth; Andrew J. Hamilton (Hydrobiologia, 2013)

Extra-Hepatic Cancer Represses Hepatic Drug Metabolism Via Interleukin (IL)-6 Signalling - Marina Kacevska; Andre Mahns; Rohini Sharma; Stephen J. Clarke; Graham R. Robertson; Christopher Liddle (Pharmaceutical Research, 2013)

Effects of Age on Mechanical Properties of Dorsiflexor and Plantarflexor Muscles - Christopher J. Hasson; Graham E. Caldwell (Annals of Biomedical Engineering, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Out-burst flood (lahar) triggered by retrogressive landsliding, 18 March 2007 at Mt Ruapehu, New Zealand—a successful early warning - Christopher I. Massey; Vernon Manville; Graham H. Hancox; Harry J. Keys; Colin Lawrence; Mauri McSaveney (Landslides, 2010)

Amelioration of ketamine-induced working memory deficits by dopamine D1 receptor agonists - Brooke M. Roberts; Patricia A. Seymour; Christopher J. Schmidt; Graham V. Williams; Stacy A. Castner (Psychopharmacology, 2010)

Scaling of plantarflexor muscle activity and postural time-to-contact in response to upper-body perturbations in young and older adults - Christopher J. Hasson; Graham E. Caldwell; Richard E. A. Van Emmerik (Experimental Brain Research, 2009)

Molecular characterisation of a cypovirus isolated from the western spruce budworm Choristoneura occidentalis - Robert I. Graham; Benoit Morin; Renée Lapointe; Vincent G. Nealis; Christopher J. Lucarotti (Archives of Virology, 2008)

Gold nanoparticles decorated with oligo(ethylene glycol) thiols: kinetics of colloid aggregation driven by depletion forces - Fajun Zhang; Donald G. Dressen; Maximilian W. A. Skoda; Robert M. J. Jacobs; Stefan Zorn; Richard A. Martin; Christopher M. Martin; Graham F. Clark; Frank Schreiber (European Biophysics Journal, 2008)

Role for the Ankyrin eukaryotic‐like genes of Legionella pneumophila in parasitism of protozoan hosts and human macrophages - Fabien Habyarimana; Souhaila Al‐khodor; Awdhesh Kalia; James E. Graham; Christopher T. Price; Maria Teresa Garcia; Yousef Abu Kwaik (Environmental Microbiology, 2008)
Summary Legionella pneumophila is a ubiquitous organism in the aquatic environment where it is capable of invasion and intracellular proliferation within various protozoan species and is also capable of causing pneumonia in humans. In silico analysis showed that the three sequenced L. pneumophila genomes each contained a common multigene family of 11 ankyrin ( ank ) genes encoding proteins with ∼30–35 amino acid tandem Ankyrin repeats that are involved in protein–protein interactions in eukaryotic cells. To examine whether the ank genes are involved in tropism of protozoan hosts, we have constructed isogenic mutants of L. pneumophila in ten of the ank genes. Among the mutants, the Δ ankH and Δ ankJ mutants exhibit significant defects in robust intracellular replication within A. polyphaga , Hartmanella vermiformis and Tetrahymena pyriformis . A similar defect is also exhibited in human macrophages. Most of the ank genes are upregulated by L. pneumophila upon growth transition into the post‐exponential phase in vitro and within Acanthamoeba polyphaga , and this upregulation is mediated, at least in part, by RpoS. Single‐cell analyses have shown that upon co‐infection of the wild‐type strain with the ankH or ankJ mutant, the replication defect of the mutant is rescued within communal phagosomes harbouring the wild‐type strain, similar to dot/icm mutants. Therefore, at least two of the L. pneumophila eukaryotic‐like Ank proteins play a role in intracellular replication of L. pneumophila within amoeba, ciliated protozoa and human macrophages. The Ank proteins may not be involved in host tropism in the aquatic environment. Many of the L. pneumophila eukaryotic‐like ank genes are triggered upon growth transition into post‐exponential phase in vitro as well as within A. polyphaga. Our data suggest a role for AnkH and AnkJ in modulation of phagosome biogenesis by L. pneumophila independent of evasion of lysosomal fusion and recruitment of the rough endoplasmic reticulum.

Methane bubbles in surface peat cores: in situ measurements - CHRISTOPHER GRAHAM LAING; TIMOTHY GEORGE SHREEVE; DEBORAH MARIE ELIZABETH PEARCE (Global Change Biology, 2008)
The quantification of greenhouse gas sources and sinks is important to understanding the impact of climate change. Methane (CH 4 ) is a potent greenhouse gas, which, on a global scale, is released largely as a product of anaerobic microbial decomposition and predominantly from wetlands. A zone of intense CH 4 production just below the water table is thought to contribute significantly to the overall flux from peat bogs. We describe the use of membrane inlet quadrupole mass spectrometry (QMS) to confirm the existence of bubbles, their gaseous concentrations and their localization at a fine spatial resolution within intact peat cores. We use the distribution of the noble gas argon (Ar) and the distinct QMS responses to dissolved and gaseous (bubble) phases to identify trapped bubbles with a resolution of 0.6 mm. Bubbles with CH 4 concentrations of up to 20 kPa were widely distributed in the upper 300 mm of the cores with ∼11% of all profiles comprising bubbles. The dissolved concentrations responsible for the bubbles were on average 83±80 μ m , indicating lower concentrations relative to other QMS studies. We suggest that if the distinction between dissolved and gaseous phases is not made in studies of CH 4 within peat profiles then the prominence of bubbles is likely to result in overestimates of dissolved CH 4 concentrations. Fluxes of CH 4 from peat as a result of drawdown or other perturbation are likely to be large, rapid and short lived because of bubble burst, and also larger than from peat without bubbles. We suggest that the dynamics of fluxes need to be modelled taking into account both gaseous and dissolved phases. Estimates of potential fluxes that assume CH 4 is dissolved are likely to overestimate fluxes if the gaseous phase has not been taken into account.

Historical changes in the phenology of British Odonata are related to climate - CHRISTOPHER HASSALL; DAVID J. THOMPSON; GRAHAM C. FRENCH; IAN F. HARVEY (Global Change Biology, 2007)
Responses of biota to climate change take a number of forms including distributional shifts, behavioural changes and life history changes. This study examined an extensive set of biological records to investigate changes in the timing of life history transitions (specifically emergence) in British Odonata between 1960 and 2004. The results show that there has been a significant, consistent advance in phenology in the taxon as a whole over the period of warming that is mediated by life history traits. British odonates significantly advanced the leading edge (first quartile date) of the flight period by a mean of 1.51 ±0.060 (SEM, n =17) days per decade or 3.08±1.16 (SEM, n =17) days per degree rise in temperature when phylogeny is controlled for. This study represents the first review of changes in odonate phenology in relation to climate change. The results suggest that the damped temperature oscillations experienced by aquatic organisms compared with terrestrial organisms are sufficient to evoke phenological responses similar to those of purely terrestrial taxa.

Historical changes in the phenology of British Odonata are related to climate - CHRISTOPHER HASSALL; DAVID J. THOMPSON; GRAHAM C. FRENCH; IAN F. HARVEY (Global Change Biology, 2007)

On the elusiveness of enemy-free space: spatial, temporal, and host-plant-related variation in parasitoid attack rates on three gallmakers of goldenrods - Stephen B. Heard; John O. Stireman; John D. Nason; Graham H. Cox; Christopher R. Kolacz; Jonathan M. Brown (Oecologia, 2006)

Intracranial injections induce local transcription of a gene encoding precerebellin-like protein - Lena Gerwick; Graham E. Corley-Smith; Miki Nakao; Jeff Watson; Christopher J. Bayne (Fish Physiology and Biochemistry, 2005)

Forms and accumulation of soil P in natural and recently restored peatlands—Upper Klamath Lake, Oregon, USA - Sean A. Graham; Christopher B. Craft; Paul V. McCormick; Allison Aldous (Wetlands, 2005)

Sugarcane biotechnology: The challenges and opportunities - Prakash Lakshmanan; R. Jason Geijskes; Karen S. Aitken; Christopher L. P. Grof; Graham D. Bonnett; Grant R. Smith (In Vitro Cellular & Developmental Biology - Plant, 2005)

Effects of halothane, isoflurane, sevoflurane and desflurane on contraction of ventricular myocytes from streptozotocin-induced diabetic rats - Mark Graham; Anwar Qureshi; Rabiah Noueihed; Simon Harrison; Frank Christopher Howarth (Molecular and Cellular Biochemistry, 2004)

Identification of Differentially Expressed Transcripts from Maturing Stem of Sugarcane by in silico Analysis of Stem Expressed Sequence Tags and Gene Expression Profiling - Rosanne E. Casu; Christine M. Dimmock; Scott C. Chapman; Christopher P.L. Grof; C. Lynne McIntyre; Graham D. Bonnett; John M. Manners (Plant Molecular Biology, 2004)

Nicotine and its withdrawal alter feeding induced by paraventricular hypothalamic injections of neuropeptide Y in Sprague-Dawley rats - Christopher Bishop; Graham Parker; Donald Coscina (Psychopharmacology, 2002)

Population-Based Evaluation of the Ehrlichia Ruminantium MAP 1B Indirect ELISA - Trevor F. Peter; Christopher J. O'Callaghan; Graham F. Medley; Brian D. Perry; Shalt M. Semu; Suman M. Mahan (Experimental and Applied Acarology, 2001)

Simulated moderate altitude elevates serum erythropoietin but does not increase reticulocyte production in well-trained runners - Michael J. Ashenden; Christopher J. Gore; Geoffrey P. Dobson; Tanya T. Boston; Robin Parisotto; Kerry R. Emslie; Graham J. Trout; Allan G. Hahn (European Journal of Applied Physiology, 2000)